Data-driven analytics for cyber-threat intelligence and information sharing. Issue 67 (June 2017) - Qamar, Sara; Anwar, Zahid; Rahman, Mohammad Ashiqur; Al-Shaer, Ehab; Chu, Bei-Tseng
Abstract: Efficient analysis of shared Cyber Threat Intelligence (CTI) information is crucial for network risk assessment and security hardening. There is a growing interest in implementing a proactive line of defense through threat profiling. However, determining the resiliency of a particular network with respect to relevant threats reported in CTI shared data remains a challenge, largely due to the lack of semantics and contextual information present in textual representations of the threat knowledge. To overcome the limitations of existing CTI frameworks, we devise a threat analytics framework based on Web Ontology Language (OWL) for formal specification, semantic reasoning, and contextual analysis, allowing the derivation of network associated threats from large volumes of shared threat feeds. Our ontology represents constructs of Structured Threat Information eXpression (STIX) with the additional concepts of Cyber Observable eXpression (CybOX), network configurations, and Common Vulnerabilities and Exposure (CVE) for risk analysis and threat actor profiling. The framework provides an automated mechanism to investigate cyber threats targeting the network under question by classifying the threat relevance, determining threat likelihood, identifying the affected and exposed assets through formulated rules and inferences. We perform a comprehensive structural and conceptual evaluation of critical advanced persistent threats (APTs) collected from credible sources and determine their relevance and risk posed to realistic network case studies. Finally we show that the proposed framework is novel in the type of analytics it provides and outperforms other competing approaches in terms of efficiency and effectiveness.